The aged brain: genesis and fate of residual progenitor cells in the subventricular zone - Capilla-Gonzalez, Vivian; Herranz-Pérez, Vicente; García-Verdugo, Jose Manuel (Frontiers in Cellular Neuroscience, 2015)
Neural stem cells persist in the adult mammalian brain through life. The subventricular zone is the largest source of stem cells in the nervous system, and continuously generates new neuronal and glial cells involved in brain regeneration. During aging, the germinal potential of the subventricular zone suffers a widespread decline, but the causes of this turn down are not fully understood. This review provides a compilation of the current knowledge about the age-related changes in the neural stem cell population, as well as the fate of the newly generated cells in the aged brain. It is known that the neurogenic capacity is clearly disrupted during aging, while the production of oligodendroglial cells is not compromised. Interestingly, the human brain seems to primarily preserve the ability to produce new oligodendrocytes instead of neurons, which could be related to the development of neurological disorders. Further studies in this matter are required to improve our understanding and the current strategies for fighting neurological diseases associated with senescence.